Application of Multi-Way Communication Interaction Patterns in Creativity Applications at PAUD Kutilang Kadugenep Kidul (Serang-Banten) - Ratih Pertiwi; Putri Anggraeni Widyastuti; Tri Wahyudi; Teguh Imanto (Jurnal Abdimas Komunikasi dan Bahasa, 2022)
The learning system implemented by PAUD with the aim of learning outcomes in accordance with the core and basic competencies that must be achieved by PAUD students in general. The growth and development of these students is in accordance with the basic and core competencies contained in the 2013 curriculum. Seeing conditions like this, the FDIK UEU community service team carried out a design in the form of a stimulus that can be used to stimulate Kutilang PAUD students. By applying the pattern of multi-way communication interaction as a method of implementing and delivering messages through creative applications that aim to get students to get the message as a whole. The conclusion that results from the implementation of this service is that multi-way communication interactions are needed aimed at the learning process of PAUD students as supporters of the cognitive creativity process of early childhood.